Congenital syphilis in a philanthropic maternity of the state of Sergipe: still a challenge - Santos, Rafael Silva; Lopes, Izailza Matos Dantas; Lopes, Adriana Dantas; Lima, Sonia Oliveira; Reis, Francisco Prado (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Syphilis is a bacterial disease whose main means of contamination are the transplacental and sexual pathways. Its high prevalence in pregnancy in Brazil makes it a national public health issue. Objective: To evaluate the positivity of the mandatory testing recommended by the Brazilian Ministry of Health (MoH) in children of VDRL-positive mothers, using data from a congenital syphilis clinic in a Philanthropic Maternity of Aracaju, Sergipe (SE). Methods: Observational, longitudinal and descriptive design, following the MoH’ congenital syphilis elimination program protocol (2006). Live births of VDRL-positive mothers were included from January 2010 to December 2014. Data analysis was performed using SPSS v21.0. Results: A total of 428 newborns (NB) were evaluated; 395 long-bone r-rays were carried out, of which, 7.3% had radiological alterations. VDRL positivity was found in cerebrospinal fluid (2.7%) and in peripheral blood (70.3%). The ear testing was altered in 3.0% and the examination of the eye fundus altered in 2.5%. The chance of having bone changes was greater in those who were born weighing from 1 to 2.5 kg and in those who presented with syphilis symptoms. Cerebrospinal fluid positivity was higher in those who had bone changes, were symptomatic, and whose partners were not treated. Maternal treatment decreased the chance of bone changes in infants. Conclusion: The non-treponemal test, VDRL, in peripheral blood was the most significant in the identification of the vertical transmission, corresponding to 70.3% of the identified samples, suggesting that its use had a greater diagnostic sensitivity, being the long bones radiography, ear test, and eye fundus test complementary in screening children of VDRL-positive mothers. In addition, the outpatient follow-up was statistically significant (p<0.01) in reducing the patients’ morbidity and mortality. This reinforces the importance of updating the guidelines for Congenital Syphilis management by the Ministry of Health, used in the institution at the time of the study, aiming to eradicate this disease that still persists despite almost seven decades of penicillin usage.